Combination Compositions Composed of l-Glutamine and Si-Jun-Zi-Tang Might Be a Preferable Choice for 5-Fluorouracil-Induced Intestinal Mucositis: An Exploration in a Mouse Model - Qu, Liping; Tan, Wanxian; Yang, Jing; Lai, Limin; Liu, Sili; Wu, Jianming; Zou, Wenjun (Frontiers in Pharmacology, 2020)
Intestinal mucositis is a common toxicity of many anti-neoplastic therapies that negatively influences health, the quality of life, economic outcomes and even the success of cancer treatment. Unfortunately, there is presently no optimal medicine that is able to effectively manage this condition. L-glutamine is one of the most frequently used agent in practice among the limited treatment choices due to its safety and inexpensiveness despite there being a lack of evidence. Previous studies indicated that L-glutamine may alleviate mucositis and mucosal atrophy but failed to improve patients’ macroscopic conditions, such as the occurrence of diarrhoea. A compound glutamine capsule (G-SJZ), composed of L-glutamine and the traditional Chinese herbal formula Si-Jun-Zi-Tang, has been used in China for 23 years to treat many types of gastrointestinal diseases, including infectious diarrhoea. However, the exact effect of G-SJZ on intestinal mucositis is unclear, and moreover, whether L-glutamine combined with Si-Jun-Zi-Tang is more effective than L-glutamine alone have not been studied. In the current study, we explored the effects of G-SJZ and L-glutamine in a mouse model of intestinal mucositis induced by 5-fluorouracil (5-Fu). The results revealed that pretreatment with G-SJZ ameliorated the physical manifestations of weight loss and the severity of diarrhoea following continuous 5-Fu injections in mice. Likewise, the histopathological damage and the destruction of villus and crypt structures in the intestinal mucosa as well as the increase in circulating intestinal injury markers caused by 5-Fu were reversed with G-SJZ pretreatment. Furthermore, the protective effect of G-SJZ was accompanied by modulations in the immunohistochemical expression of tight junction proteins. Interestingly, although treatment with a dose of L-glutamine alone that was equivalent to the dose in G-SJZ also showed a protective effect, it did not appear to be as strong as treatment with G-SJZ. Si-Jun-Zi-Tang in G-SJZ may compensate for the deficiencies of L-glutamine in this model despite exact mechanism still needs further study. Our study is the first to suggest that the combined use of L-glutamine and Si-Jun-Zi-Tang might be more effective than L-glutamine alone. Because of the limited number of therapeutic agents, G-SJZ is likely to be a preferable choice for intestinal